Investigation on the Deposition of Conductive Ink on Multiple Substrates with Different Substrate Surface Energy and Ink Surface Tension Properties - Yuen Hern, Loo; Khirotdin, Rd Khairilhijra'; Hassan, Nurhafizzah (International Journal of Integrated Engineering, 2025)
Conductive ink is a transformative material that enables the printing of electronic circuits on a variety of substrates, revolutionizing the field of printed electronics. This study addresses the limitation of existing mathematical models for conductive ink deposition, which primarily assume ink deposition solely on generic substrates and printing on the fly, thus lacking adaptability for diverse applications. The objective is to integrate substrate surface energy and ink surface tension into mathematical model thus improve the precision of ink track width estimation. Employing a syringe deposition system, data analysis was conducted to develop an improved mathematical model that predicts ink deposition on various substrates while establishing optimal printing parameters. Experimental results indicated significant discrepancies in line widths, with initial measurements exceeding 2 mm and percentage errors surpassing 150%. By incorporating SSE, the improved model achieved line widths between 0.72 mm and 0.92 mm, significantly reducing the maximum error to 15.82%. The findings emphasize the crucial influence of substrate surface energy and ink surface tension on ink spreading and adhesion, particularly on substrates with varying porosity and absorbency.